Loss of Neuron-Astroglial Interaction Rapidly Induces Protective CNTF Expression after Stroke in Mice - Kang, Seong Su (Society for Neuroscience, 2012)
Ciliary neurotrophic factor (CNTF) is a potent neural cytokine with very low expression in the CNS, predominantly by astrocytes. CNTF increases rapidly and greatly following traumatic or ischemic injury. Understanding the underlying mechanisms would help to design pharmacological treatments to increase endogenous CNTF levels for neuroprotection. Here, we show that astroglial CNTF expression in the adult mouse striatum is increased twofold within 1 h and increases up to >30-fold over 2 weeks following a focal stroke caused by a transient middle cerebral artery occlusion (MCAO). Selective neuronal loss caused by intrastriatal injection of quinolinic acid resulted in a comparable increase. Cocultured neurons reduced CNTF expression in astrocytes, which was prevented by light trypsinization. RGD (arginine-glycine-aspartic acid) blocking peptides induced CNTF expression, which was dependent on transcription. Astroglial CNTF expression was not affected by diffusible neuronal molecules or by neurotransmitters. The transient ischemia does not seem to directly increase CNTF, as intrastriatal injection of an ischemic solution or exposure of naive mice or cultured cells to severe hypoxia had minimal effects. Inflammatory mechanisms were probably also not involved, as intrastriatal injection of proinflammatory cytokines (IFNγ, IL6) in naive mice had no or small effects, and anti-inflammatory treatments did not diminish the increase in CNTF after MCAO. CNTF−/− mice had more extensive tissue loss and similar astrocyte activation after MCAO than their wild-type littermates. These data suggest that contact-mediated integrin signaling between neurons and astrocytes normally represses CNTF expression and that neuronal dysfunction causes a rapid protective response by the CNS.